Depressive Symptoms and Addictive Behaviors in Young Adults After Childhood Trauma: The Mediating Role of Personality Organization and Despair - Fuchshuber, Jürgen; Hiebler-Ragger, Michaela; Kresse, Adelheid; Kapfhammer, Hans-Peter; Unterrainer, Human F. (Frontiers in Psychiatry, 2018)
Background: There is substantial evidence that traumatic experiences in childhood increase the likelihood of mood pathology and addictive behaviors in adolescence and young adulthood. Furthermore, both forms of psychopathology have been linked to deficiencies in personality organization and a common primary emotion core. In this study, we intended to further investigate these interactions by assuming a mediating role of personality organization and despair regarding the relationship between childhood trauma and psychiatric symptom burden later in life. Methods: A total sample of 500 young adults (Age: M = 26; SD = 5.51; 63.2% female) were investigated. Structural equation modeling was applied in order to investigate the pathways between the latent variables Childhood Trauma, Structural Deficit, Despair (comprised of the primary emotions SEEKING and SADNESS), as well as symptoms of addiction and depression. Results: The results indicate that the influence of Childhood Trauma on Addictive Behaviors was mediated by Structural Deficit (p < .01), whereas its influence on Depressive Symptoms was mediated by Despair (decreased SEEKING and increased SADNESS) (p < .01). Furthermore, Addictive Behaviors seemed to be stronger represented in males (p < .001). The final model was able to explain 39% of the variance of Addictive Behaviors and 85% of the variance of Depressive Symptoms. Discussion: The findings underline the importance of early experiences in the development of adult affective and personality functioning, which is linked to the development of psychiatric disorders. Regarding clinical practice, addiction treatment might focus on the improvement of personality organization, while treatment of depressed patients should primarily emphasize the restructuring of dysfunctional primary emotion dispositions.